FAKTOR - FAKTOR YANG MEMENGARUHI PENGGUNAAN ALAT KONTRASEPSI PADA WANITA USIA SUBUR DI KECAMATAN DUREN SAWIT PADA PANDEMICOVID-19 TAHUN 2022 - Ester Liana, (2022)
The Family Planning Program is a program to control Indonesia's population in order to reduce population density and improve human resource quality. Before the pandemic, Indonesia had a birth rate of 2.6, which is higher than the ASEAN average of 2.4. During the pandemic, there was a decreation in contraceptive use due to Large-Scale Social Restrictions, which caused health service facilities to be limited, potentially causing a decrease in user. A cross-sectional study was adopted as the research design. Population of this study from Women of Childbearing Age (WCA) residents of Duren Sawit District, and purposive sampling technique used to get 290 samples. The analysis data in this study was multivariate analysis with multiple logistic regression. This study held from April to May 2022. The study found a link between the independent factors of income, knowledge, health staff support, and husband's support to the dependent variable which contraceptive use. Multiple logistic regression analysis revealed that the husband variable, with a POR of 21.08 (95 % CI 8.70-51.07), was the most important factor influencing contraceptive use in WCA. Conclusion, WCA who have their husband's support will use contraception 21.08 times more than WCA who do not have their husband's support. Keywords: Contraception devices, Determinants of COVID-19 family planning, and Family planning